Prenatal Course and Sonographic Features of Congenital Mesoblastic Nephroma - Theera Tongsong; Watchareepohn Palangmonthip; Wisit Chankhunaphas; Suchaya Luewan (Diagnostics, 2022)
Background: Congenital mesoblastic nephroma (CMN) is the most common renal tumor among fetuses and infants before the age of 6 months. It usually behaves as a benign tumor. The prenatal features and outcomes of pregnancies with fetal CMN have never been systematically reviewed and analyzed, whereas neonatal or pediatric series have been published several times. The aims of this study are to (1) describe the prenatal natural course and prenatal sonographic char-acteristics of CMN; (2) determine the outcomes of pregnancies with fetal CMN; and (3) demonstrate typical sonographic images together with video clips of prenatal CMN, as an educational example based on our index case presented here. Methods: Studies focused on fetal CMN, including those consecutively published on PubMed from 1980 to June 2022 as well as the index case presented here, were identified and validated to perform a systematic review. The data of fetal imaging and the prenatal course of pregnancies were extracted for analysis. Results: The findings derived from 41 cases of review are as follows: (1) No single case has been diagnosed in the first half of pregnancy. No cases were detected during routine anomaly screening at mid-pregnancy. All cases were de-tected in the third trimester or late second trimester. (2) Polyhydramnios is very common and is the first clinical manifestation in most cases, leading to detailed ultrasound in the second half of pregnancy. (3) Preterm birth and low birth weight are the most common adverse pregnancy out-comes, resulting in neonatal morbidity. (4) Hydrops fetalis, though relatively rare, can be associated with CMN and is a grave sign. (5) Prenatal diagnosis is essential since it is critical for the antenatal plan, comprising either referral to a tertiary care center or proper surveillance to prevent serious obstetric complications, especially preterm birth. (6) Ultrasound is the primary tool for prenatal diagnosis of CMN, whereas MRI can be used as an adjunct if some other tumors are suspicious or sonographic features are not typical for CMN. Conclusion: In contrast to CMN in neonates, fetal CMN is much more serious since it significantly impacts adverse pregnancy outcomes and perinatal morbidity and mortality. The typical prenatal course and the sonographic features of CMN are described.